Transnacionalismus a inkluze do majoritní společnosti: Neslučitelné perspektivy? Metodologická úvaha nad přístupy k migrantům - Jirka, Luděk (Lidé města, 2016)
Many researchers are aimed at assimilation/integration which means research concern with immigrant incorporation into the majority society. Compared to transnationalism, researchers concerned in transnational ties are aimed at ties between immigrant and his country of origin. However, early concepts of transnationalism were too „radical“ in respond to integration/ assimilation and there were developed concepts of transnationalism which obstructed the links towards majority society/country of destination. There were two main methodological problems. Firstly, there was refusing of influences of nation state towards immigrants and secondly, there was ethnicization or nationalization of migrants in term of groupness. Because of this, approaches of transnationalism and integration/assimilation can be seen as antithetical – but they are antithetical only in the minds of researchers. As we can see from the constructivist critique of transnationalism during last years, transnational ties can be consistent with inclusion and many researches from abroad proved this stance. In spite of constructivist critique during last years, early concepts of transnationalism are still widespread in Czech social sciences. It means that Czech social sciences are engaged in theories of transnationalism which do not admit ties with the majority society.